An All-sky Survey of White Dwarf Merger Remnants: Far-Ultraviolet Is the Key - Mukremin Kilic; Pierre Bergeron; Warren R. Brown; Simon Blouin; Gracyn Jewett; Adam Moss; Patrick Dufour; Olivier Vincent (The Astrophysical Journal)
The majority of merging white dwarfs leave behind a white dwarf remnant. Hot/warm DQ white dwarfs with carbon-rich atmospheres have high masses and unusual kinematics. All evidence points to a merger origin. Here, we demonstrate that far-UV (FUV) and optical photometry provides an efficient way to identify these merger remnants. We take advantage of this photometric selection to identify 167 candidates in the Galaxy Evolution Explorer All-Sky Imaging Survey footprint, and provide follow-up spectroscopy. Out of the 140 with spectral classifications, we identify 75 warm DQ white dwarfs with T _eff  > 10,000 K, nearly tripling the number of such objects known. Our sample includes 13 DAQ white dwarfs with spectra dominated by hydrogen and (weaker) carbon lines. Ten of these are new discoveries, including the hottest DAQ known to date, with T _eff  ≈ 23,000 K and M  = 1.31 M _⊙ . We provide a model atmosphere analysis of all warm DQ white dwarfs found, and present their temperature and mass distributions. The sample mean and standard deviation are T _eff  = 14,560 ± 1970 K and M  = 1.11 ± 0.09 M _⊙ . Warm DQs are roughly twice as massive as the classical DQs found at cooler temperatures. All warm DQs are found on or near the crystallization sequence. Even though their estimated cooling ages are of order 1 Gyr, their kinematics indicate an origin in the thick disk or halo. Hence, they are likely stuck on the crystallization sequence for ∼10 Gyr due to significant cooling delays from distillation of neutron-rich impurities. Future all-sky FUV surveys like Ultraviolet Explorer have the potential to significantly expand this sample.